2022
DOI: 10.3390/ijms23031234
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into miR-1290: An Oncogenic miRNA with Diagnostic Potential

Abstract: For more than two decades, the view of the roles of non-coding RNAs (ncRNAs) has been radically changing. These RNA molecules that are transcribed from our genome do not have the capacity to encode proteins, but are critical regulators of gene expression at different levels. Our knowledge is constantly enriched by new reports revealing the role of these new molecular players in the development of many pathological conditions, including cancer. One of the ncRNA classes includes short RNA molecules called microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 275 publications
(337 reference statements)
0
4
0
Order By: Relevance
“…32 Additionally, two probe−target pairs were used in this study to further demonstrate the modularity of the system, both of which are DNA analogues of known miRNA biomarkers against cancer: i.e., miR-155 57 and miR-1290. 58 Although DNA was used for this study, since it is more stable than RNA, future studies can be carried out using different types of nucleic acids, e.g., viral RNA, miRNA, or cell-free DNA. Moreover, a comparison between chimeras bearing the amino acid-based GGG linker and the chemical modification O linker both showed strong binding affinities to the gold substrate, similar hybridization kinetics, and viscoelastic properties expected from flexible molecules.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Additionally, two probe−target pairs were used in this study to further demonstrate the modularity of the system, both of which are DNA analogues of known miRNA biomarkers against cancer: i.e., miR-155 57 and miR-1290. 58 Although DNA was used for this study, since it is more stable than RNA, future studies can be carried out using different types of nucleic acids, e.g., viral RNA, miRNA, or cell-free DNA. Moreover, a comparison between chimeras bearing the amino acid-based GGG linker and the chemical modification O linker both showed strong binding affinities to the gold substrate, similar hybridization kinetics, and viscoelastic properties expected from flexible molecules.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Additionally, two probe–target pairs were used in this study to further demonstrate the modularity of the system, both of which are DNA analogues of known miRNA biomarkers against cancer: i.e., miR-155 and miR-1290 . Although DNA was used for this study, since it is more stable than RNA, future studies can be carried out using different types of nucleic acids, e.g., viral RNA, miRNA, or cell-free DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR-107 protects against inflammation and apoptosis of endothelial cells via KRT1-dependent Notch signaling pathway [ 54 ] whereas hsa-let-7b-5p regulates neutrophil function and reduces neutrophilic inflammation by suppressing the canonical TLR4/NF-κB pathway [ 55 ]. Lastly, hsa-miR-1290 is directly related to the differentiation status of MSC undergoing chondrogenic differentiation indicating its putative chondroprotective and anabolic effects for cartilage regeneration in vivo [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Based on recent research, miR-663b serves as an oncomir, and its suppression has the potential to diminish cell migration and proliferation; However, its precise role in various types of cancer remains unknown [ 47 ]. In previous studies has been reported that miR-1305 is a tumor suppressor that can downregulate the downstream oncogenic genes [ [47] , [48] , [49] , [50] ]. Therefore, the upregulation of circ_0087558 may contribute to the overexpression of PHLDA by the change in miR-1305 expression .…”
Section: Discussionmentioning
confidence: 99%